Orzeczenie o winie w rozkładzie pożycia jako element treści cywilnego wyroku rozwodowego - Krawczyk, Michał (Ius Matrimoniale, 2018)
According to art. 57 § 1 of the Family and Guardianship Code, the court decides if the spouse and which one is to blame for the breakdown of the decree. According to § 2 of the cited article, on the courtesy of the spouses, the court will not adjudicate on guilt. It should be emphasized that the issue of guilt in divorce can only be settled in a divorce decree. If the divorce decree did not contain a decision regarding guilt, it can not be decided in a separate trial. The verdict on guilt is a sort of summary and assessment of a shared life. Therefore, its justification should be particularly balanced and comprehensively argued. Determining the guilt of one of the spouses, however, has not only a moral overtone but it is also a premise for other decisions, in particular, adjudication of maintenance for the spouse, and even for a possible request to establish unequal shares in the joint property.